Vidas anarquistas / Gustavo Vidal Manzanares - Vidal Manzanares, Gustavo (1972-) (Cuadernos libertarios ; 6)
Habla de Joseph Hillstrom (Joe Hill), Francisco Ferrer y Guardia, Edgardo Ricetti, Nicola Sacco, Bartolomé Vanzetti, Francisco Granado, Joaquín Delgado, Joaquín Penina, Fermín Salvochea, Lope Massaguer, Antonia Lisbona y Miguel Grau | Bibliografía: p. 115